Integration of Al Farabi's Perspective Happiness Values in the Islamic Counseling Process as an Effort to Achieve Quality of Life - Alfi Rahmi; Sufyarma Marsidin; Yeni Karneli (Islamic Counseling: Jurnal Bimbingan dan Konseling Islam, 2023)
The purpose of this study examines how the integration of the value of happiness in Al Farabi's perspective is created through the process of Islamic counseling so that a good quality of life can be achieved. Al Farabi defines a happy quality of life obtained through a correct understanding of the purpose of a life lived, namely eternal happiness in the hereafter by showing good moral behavior. Islamic counseling is an effort to help humans achieve happiness in life. The research method is in the form of a literature study through content analysis in the literature that is relevant to the research objectives. The results of the study found that the stages of the Islamic counseling process that can be passed to help achieve the value of happiness from Al Farabi's perspective are the stages of understanding the meaning of the value of happiness from clients, identifying problems that interfere with the client's life happiness, the stage of developing solutions or the stage of coaching clients, and the evaluation stage. This stage is supported by techniques for understanding the meaning of life, techniques for dealing with stress and anxiety in life, techniques for maintaining the quality of social relations because humans are social beings, and techniques for hoping and praying that every problem has a solution following Islamic teachings and spirituality techniques.